Effect of Soilless Media (Hydroponic ) on Growth and Yield of Two Varieties of Lettuce - Jhon Hardy Purba; I Putu Parmila; Wayan Dadi (Faculty of Agriculture, Merdeka University Surabaya, 2021)
The purpose of this study was to determine the effect of media types, varieties and their combinations on the growth and yield of lettuce with hydroponic wick system cultivation. This research was carried out in the agronet house of the Agrotechnology Study Program, Faculty of Agriculture, Panji Sakti University, Singaraja with an altitude of 39 meters above sea level (above sea level) from May to July 2019. The experimental design used in this study was factorial randomized block design (RBD) which consisted of two factors, the first factor was growing media in a net pot (M) with 3 types, namely rockwool growing media (M1); husk charcoal growing media (M2), and coco peat growing media (M3), and the second factor is the variety (V) which consists of 2 types, namely the frizzy lettuce (V1) and the red lettuce (V2). The results of this study showed that the best medium which gave greater result was husk charcoal medium and compared to rockwool and cocopeat, the frizzy lettuce was better than the red lettuce, and the combination of the husk charcoal medium and the frizzy lettuce variety gave the best growth and yield parameters.